Cognitive technologies - DAVENPORT, Tom (Institutional Knowledge at Singapore Management University, 2024)
AI and the revolution of work.Professor Tom Davenport, the President’s Distinguished Professor of Information Technology and Management at Babson College, speaks about how companies can integrate generative Artificial Intelligence (GenAI) into their operations while ensuring workforce adaptation and skills development.